MYELOPROLIFERATIVE NEOPLASMS IN PATIENTS YOUNGER THAN 40 YEARS: A RETROSPECTIVE ANALYSIS OF CLINICAL CHARACTERISTICS - Arsenović, Isidora; Smiljanić, Mihailo; Kecman, Natalija; Lemajić, Nikola; Jovanović, Jelica; Đorđević, Vesna; Šefer, Dijana; Peruničić-Jovanović, Maja; Jaković, Ljubomir; Bogdanović, Andrija; Leković, Danijela (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Myeloproliferative neoplasms (MPN) are typically diagnosed in patients around 60 years of age; however, in clinical practice, patients  18 cm. This indicates the need for better stratification and the use of different methods for disease risk assessment, such as next-generation sequencing (NGS).
Keywords: myeloproliferative neoplasms; thrombosis; adolescents; young age